Pathogenity Test Bacteria Pasteurella multocida Local Isolate Using Postulate Koch - Herliani Herliani; Abrani Sulaiman; Muhammad Ilmi Hidayat; Ananda Mellyani Hidayat (Journal of Wetlands Environmental Management, 2018)
The study aimed to find out whether Pasteurella multocida bacteria isolated from buffalo in HSU (Hulu Sungai Utara) is the cause of SE (SepticemaÂ  epizootica) disease in swamp buffaloes using Koch Postulates. Total of 10 Balb-C mice aged 2 weeks were infected with 100 Î¼l culture containing 4 x 108 CFU (1.5 McFarland Scale) P. multocida subcutaneously in the neck , and observed every 4 hours until the animal died. Samples were taken from the spleen, lungs, and heart with different times of death within 15 hours, 35 hours, and 59 hours with sterile swab cotton. Samples were grown on a nutrient broth medium (NB), inoculated on a soy trypticase agar (TSA), and incubated for 24 hours at 37 Â° C. Separate colonies were stained with Gram and spore staining. The colonies were tested by catalase, biochemical, indol motility (SIM) sulfite, confectionary, and planted on Mac Conkey Agar media. P. multocida was identified following Carter's method of showing lung, spleen, and positively infected P. multocida samples. It was concluded that P. multocida bacteria isolated from buffalo in HSU are pathogenic and can cause SE disease.